HUBUNGAN ANTARA FASILITAS RUANG TERBUKA SEKOLAH DAN PARTRISIPASI OLAHRAGA SISWA TERHADAP PRESTASI PENJAS SISWA MTS. DI-JAWA BARAT - Purnama, Acep; Carsiwan; Tarigan, Beltasar (Jurnal Pedagogik Olahraga, 2025)
This study aims to determine the relationship between school open space facilities and student sports participation on student physical education achievement. The sustainability of student physical education achievement is influenced by facilities and sports participation. A quantitative descriptive research methodology was used in this study. Correlation tests were used in data processing to determine how the variables are related to one another. The Sport Development Index (SDI) was used as a research tool. Students from Madrasah Tsanawiah (MTs) throughout West Java were the population of this study. A total of 260 people were sampled, and data were collected using questionnaires. There were 131 female respondents and 129 male respondents. Based on the results of the explanation between variables, a value was obtained that could indicate the correlation between Open Space Facilities and Physical Education Achievement, with a correlation coefficient value (p>0.05), namely (p=0.528), but it was not significant because the Sig value (p<0.05) was (p=0.179). The analysis of the relationship between Physical Education Achievement and Sports Participation yielded a correlation coefficient (p>0.05) of (p = 0.704), which is significant because the Sig value (p<0.05) is (p = 0.051). Adequate open space facilities, such as sports fields and play areas, contribute positively to students' interest and motivation to participate in sports activities, which ultimately impacts physical education achievement.